THE USE OF TRAUMA SCORING SYSTEMS IN ELDERLY PATIENTS WHO ARE ADMITTED TO THE EMERGENCY DEPARTMENT DUE TO FALLS - (:unkn) unknown (GUNES KITABEVI LTD STI, 2014)
Introduction: The aim of our study is to review demographic characteristics, management in concordance with trauma scoring systems, and the significance of trauma scoring systems in predicting the duration of hospital stay in geriatric patients who are admitted to the emergency department because of falling. Materials and Method: This retrospective study reviewed the records of 1086 patients who were admitted to our emergency department because of falling, between February 1, 2011 and January 31, 2012. Age, gender, date and time of the admission, type of fall, diagnosis related to fall, requisition for radiological tests, requisition for consultations, and end treatment status were recorded for each patient. Glasgow Coma Score, Revised Trauma Score and Injury Severity Score were calculated. Results: Fourteen point five percent of all patients were geriatric patients. The number of hospitalized patients was 248 (22.8%) and the hospitalization period was 6.9 +/- 4.6 days. Comparison of patients according to their outcome of treatment in the emergency department (discharge or admission) showed a significantly higher mean Revised Trauma Score and significantly lower mean Injury Severity Score in the of discharged patients subgroup. Conclusion: Our results suggest that anatomic scoring systems (Injury Severity Score) are more accurate than physiological scoring systems (Revised Trauma Score, Glasgow Coma Score) in predicting the duration of hospitalization in patients with trauma due to falling. But these results may require to support by further prospective studies.
Keywords: Fall; Geriatrics; Severity of Illness Index; Predictive Value of Tests